PERANCANGAN AWAL LAMBUNG KAPAL KEPRESIDENAN DARI KOMPOSIT WOVEN KEVLAR-RAMI-POLYESTER - Budiman Adi Setyawan; Amir Marasabessy (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
The unitary state of the Republic of Indonesia consists of thousands of islands scattered from Sabang to Merauke. The foremost islands in Indonesia are rarely visited by the President of the Republic of Indonesia, which may be one of the reasons why there are no marine service vehicles such as on land and in the air. Therefore we need a very special marine vessel (VVIP) made of selected materials. Some of the requirements that must be met are light, fast, bullet proof, anti-fire, safe and comfortable for the occupants. The most important part of a ship is the hull. The hull must be made of very strong materials such as Kevlar,Polyester and Jute. These materials have been widely used for military purposes. The main material for the hull of the ship,namely Kevlar, jute and polyester composites are tested for quality to meet SNI/ISO standards. The test results on Kevlar, Polyester and Jute materials are that the weight of Kevlar HT1 is 130 g/m2 and Polyester /Jute 65/35% 210 g /m2 (SNI / ISO 3801: 2010). The tensile strength of HT1 kevlar is 5300 N/5 cm (H/V) (ISO 13934-1) and Polyester/Jute 65/35%, 885.42 N/2.5 cm (H), 403.83 N/2, 5 cm (V) (SNI 0276: 2009). The number of warp and weft of Kevlar HT1 was 10 strands / 1.0 cm (ISO 7211-2) and the amount of warp and weft Polyester /Jute 65/35% is 41 strands / 1.0 cm (V) and 22 strands / 1.0 cm (H) (SNI / ISO 7211-2: 2010). The pattern of Kevlar HT1 is plate and 65/35% Polyester /Jute is keper 2/1 (SNI / ISO 7211-1: 2010).